MODEL MEDIA IKLAN POTENSIAL YANG TEPAT SASARAN PRODUK UNGGULAN UKM - Joko Suryono (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
Goal of this research is a purpose model of the right advertising media to reach potential target markets superior products of Small and Medium Enterprises of Sukoharjo regency is acclaimed local, national, international a) Activity try model of the right advertising media to reach potential target markets superior products of Small and Medium Enterprises of Sukoharjo regency is acclaimed local, national, international b) Produce a description effectivitely of media advertising options of Small and Medium Enterprises product of Sukoharjo Regency is acclaimed local, national, international c) Produce model of the right advertising media to reach potential target markets superior products of Small and Medium Enterprises of Sukoharjo regency is acclaimed local, national, international. Type of research is to apply is theoritycal model test, model test, evaluatif studi /effectively model scale. The result is concluded advertising media to reach potential target markets superior products of Small and Medium Enterprises to 1) word of mouth to social media face book, website, blogspot, twitter, toko online, blackberry b) Advertising message in social media need high creative, big idea, advertising teks or advetising ilustration, c) Friendship comunities in social media is strategy potential target markets d) Implication development communication tecnology changes marketing media maping : from old media to new media, from phisic media to click media e) Implication tecnolgy communication development changes mass communication theory to social comunication network.